2016
DOI: 10.2147/iprp.s93312
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of a pharmacist-led inpatient anticoagulation service: a review of the literature

Abstract: BackgroundAnticoagulant therapies provide management options for potentially life-threatening thromboembolic conditions. They also carry significant safety risks, requiring careful consideration of medication dose, close monitoring, and follow-up. Inpatients are particularly at risk, considering the widespread use of anticoagulants in hospitals. This has prompted the introduction of safety goals for anticoagulants in Canada and the USA, which recommend increased pharmacist involvement to reduce patient harm. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 27 publications
0
22
0
3
Order By: Relevance
“…13,14 Also, pharmacist recommendations diminished the number of medication errors, drug interactions, and INR reading outrange, which in turn lead to higher TTR values and greater patients medication adherence. 18 A study by Aidit et al indicated that pharmacists had a positive influence on management by implementing warfarin medication-adherence clinics ith pharmacists who dedicated some of their time to education, counseling, and dealing with adherence issues. 19 Furthermore, pharmacists' accessibility for questions and communication influenced the excellent management of anticoagulation that facilitated the establishment of a community pharmacist-led anticoagulation-management service in New Zealand and the development of pharmacist community clinics for anticoagulation in some parts of the US and UK.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Also, pharmacist recommendations diminished the number of medication errors, drug interactions, and INR reading outrange, which in turn lead to higher TTR values and greater patients medication adherence. 18 A study by Aidit et al indicated that pharmacists had a positive influence on management by implementing warfarin medication-adherence clinics ith pharmacists who dedicated some of their time to education, counseling, and dealing with adherence issues. 19 Furthermore, pharmacists' accessibility for questions and communication influenced the excellent management of anticoagulation that facilitated the establishment of a community pharmacist-led anticoagulation-management service in New Zealand and the development of pharmacist community clinics for anticoagulation in some parts of the US and UK.…”
Section: Discussionmentioning
confidence: 99%
“…The PMWP resulted in improved INR for inpatient warfarin recipients and to less near-term bleeding among higher risk, surgical patients. 7 Pharmacist consultation and management of patients on warfarin therapy has shown to improve INR and reduce adverse events compared to physician-managed groups.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of pharmacist has also caused significant reduction in ADRs associated with anticoagulants. 14…”
Section: Anticoagulation Clinicsmentioning
confidence: 99%